PRAKTIK PEMBELAJARAN BAHASA INDONESIA KURIKULUM MERDEKA BERDASARKAN PERSPEKTIF FILSAFAT PROGRESIVISME (STUDI KASUS DI SMP NEGERI 1 TANGEN) - Tari, Wahyu Fajar Lestari; Deni Purwanti; Nailil Haliza Sampurno; Sarwiji Suwandi; Atikah Anindyarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The curriculum is designed, compiled, and developed based on the philosophical thinking of education, one of which is progressivism. The philosophical basis in curriculum development has a strategic and systematic role so that the curriculum developed is in line with national education goals. This study aims to describe the implementation of Indonesian language teaching and learning activities based on the Independent Curriculum reviewed from the perspective of the philosophy of progressivism education at SMP Negeri 1 Tangen, Sragen, Central Java. This study applies a qualitative descriptive approach with a case study method. Data collection techniques include observation, interviews, documentation, and literature studies as an effort to triangulate comprehensive data. This study proves that Indonesian language learning at SMP Negeri 1 Tangen has implemented the principles of progressivism, including student-centered learning, contextual and meaningful learning, differentiated learning, and the creation of a democratic learning environment. In addition, the implementation of the Pancasila Student Profile Strengthening Project (P5) also reflects the integration of progressivism values. These findings indicate that the Independent Curriculum and the philosophy of progressivism support each other in creating humanistic, adaptive, and participatory learning.